Transcription of specific auxin efflux and influx carriers drives auxin homeostasis in tobacco cells. (31st August 2019) - Müller, Karel; Hošek, Petr; Laňková, Martina; Vosolsobě, Stanislav; Malínská, Kateřina; Čarná, Mária; Fílová, Markéta; Dobrev, Petre I; Helusová, Michaela; Hoyerová, Klára; Petrášek, Jan
Summary: Auxin concentration gradients are informative for the transduction of many developmental cues, triggering downstream gene expression and other responses. The generation of auxin gradients depends significantly on cell‐to‐cell auxin transport, which is supported by the activities of auxin efflux and influx carriers. However, at the level of individual plant cell, the co‐ordination of auxin efflux and influx largely remains uncharacterized. We addressed this issue by analyzing the contribution of canonical PIN‐FORMED (PIN) proteins to the carrier‐mediated auxin efflux in Nicotiana tabacum L., cv. Bright Yellow (BY‐2) tobacco cells. We show here that a majority of canonical NtPINs are transcribed in cultured cells and in planta . Cloning of NtPIN genes and their inducible overexpression in tobacco cells uncovered high auxin efflux activity of Nt PIN11, accompanied by auxin starvation symptoms. Auxin transport parameters after NtPIN11 overexpression were further assessed using radiolabelled auxin accumulation and mathematical modelling. Unexpectedly, these experiments showed notable stimulation of auxin influx, which was accompanied by enhanced transcript levels of genes for a specific auxin influx carrier and by decreased transcript levels of other genes for auxin efflux carriers. A similar transcriptional response was observed upon removal of auxin from the culture medium, which resulted in decreased auxin efflux. Overall, our results revealed an auxin transport‐based homeostatic mechanism for the maintenance of endogenous auxin levels. Open Research Badges: This article has earned an Open Data Badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available at http://osf.io/ka97b/ Significance Statement: Numerous events during plant development are coordinated by intercellular auxin transport to establish auxin intracellular homeostasis. However, co‐operation between auxin influx and efflux activities at the cellular level is largely unexplored. In this study, we used a simplified model of cultured tobacco cells to show that a mechanism exists at the cellular level that coordinates gene expression and the activity of specific auxin influx and efflux carriers.